Myo-inositol versus D-chiro-inositol in murine in vitro follicular development: An experimental study relevant to polycystic ovary syndrome - Aika Korai; Tsuyoshi Baba; Fukiko Kasuga-Yamashita; Sachiko Nagao; Yuya Fujibe; Miyuki Morishita; Yoshika Kuno; Tasuku Mariya; Keiko Ikeda; Hiroyuki Honnma; Toshiaki Endo; Tsuyoshi Saito (PLoS ONE, 2026)
Inositol plays a crucial role in follicular development by regulating insulin signaling and ovarian function. However, its precise mechanism of action remains unclear. This study investigated the effects of myo-inositol (MI) and D-chiro-inositol (DCI) on the development of murine ovarian follicles in vitro. Follicles treated with DCI exhibited larger diameters than controls on Day 6 (275.20 ± 12.54 μm; p = 0.037) and Day 8 (277.47 ± 11.47 μm; p = 0.048), indicating a modest, marginally significant effect that was not maintained by Day 10. The rate of follicular antrum formation was significantly higher in the DCI-treated group on Day 6 (p < 0.05); however, no significant differences were observed on Days 8 and 10. In contrast, MI treatment did not affect follicular survival, diameter, or antrum formation compared with controls. Estradiol concentrations and the expression levels of follicle-stimulating hormone receptor and aromatase genes did not differ significantly among groups. Together, these data provide in vitro evidence that DCI can facilitate the transition from the secondary (preantral) to the early antral stage under these culture conditions. Given the small experimental sample size, the use of healthy murine follicles cultured under a high FSH concentration, and the absence of a PCOS-like ovarian milieu, these findings should be interpreted cautiously and cannot be directly generalized to infertility treatment in women with PCOS. Future studies using PCOS animal models and human follicle systems are needed to clarify translational relevance of these findings.